If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(n + -1) = n + 14 Reorder the terms: 4(-1 + n) = n + 14 (-1 * 4 + n * 4) = n + 14 (-4 + 4n) = n + 14 Reorder the terms: -4 + 4n = 14 + n Solving -4 + 4n = 14 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -4 + 4n + -1n = 14 + n + -1n Combine like terms: 4n + -1n = 3n -4 + 3n = 14 + n + -1n Combine like terms: n + -1n = 0 -4 + 3n = 14 + 0 -4 + 3n = 14 Add '4' to each side of the equation. -4 + 4 + 3n = 14 + 4 Combine like terms: -4 + 4 = 0 0 + 3n = 14 + 4 3n = 14 + 4 Combine like terms: 14 + 4 = 18 3n = 18 Divide each side by '3'. n = 6 Simplifying n = 6
| 4y^3-3=-12y^2+y | | 10+2z=20 | | -6+x=-10 | | 12t-1=14t-5 | | 8k+10=13k-5 | | 3v^2-7v-20= | | 3a=5a-18 | | 6(x+2)=3(x-5) | | 5x+37=14x-62 | | x^2+5x+18=9 | | 4x+7=x+16 | | 15r+22=97 | | 3(x-4)+5(x+3)=2(3x-5)-6 | | 6(2x-5)=42 | | -4x+2(4-3x)=8-10x | | 9x-21=3+3 | | 3r+12=r+34 | | 4p+8=10p+2 | | -x^2+50x-350=0 | | 8t^2-6t=9 | | x^5-x^4+9x^3-9x^2=0 | | 2x+3=24 | | 5x^2+36x+36=0 | | 6(x-8)-(2x-2)=5x-1 | | .5(20z+18)-8=9(z-3) | | 7x+19y=-3 | | -4c+1=-7 | | 12n-6=4n+10 | | 3(y+-4)+9(y+1)= | | 11m^2-2m=10 | | 4(3+c)=3(c-4) | | 8n-6=10 |